Hubungan Antara Konsep Baik dan Buruk Dalam Ilmu Kalam Dengan Konsep Maslahat Dalam Hukum Islam - Fathurrahman Djamil (Al-Jami'ah Research Centre, 1999)
There is a hypothesis that a theological school belongs to a Muslim influences his or her thought in uṣūl al-fiqh (foundation of